Near-bottom temperature data obtained from Current and Pressure-recording Inverted Echo Sounders (CPIES) and processed HYCOM data near the Chukchi slope ... - Ku, Ahyoung; Park, Jae-Hun; Jeon, Chanhyung; Peacock, Thomas; Chae, Jeong-Yeob; Park, Taewook; Cho, Kyoung-Ho (SEANOE, 2018)
Quasi-seasonal and sub-inertial variations of near-bottom temperature were observed using Current and Pressure-recording Inverted Echo Sounders (CPIES) deployed on the slope between Canada basin and the Chukchi shelf from August 2018 to July 2020.Quasi-seasonal and sub-inertial variations of near-bottom temperature were observed using Current and Pressure-recording Inverted Echo Sounders (CPIES) deployed on the slope between Canada basin and the Chukchi shelf from August 2018 to July 2020. They were equipped with a 4930R ZPulse Doppler current sensor positioned approximately 51 m above the seafloor, which measured near-bottom current and temperature. Among the variables CPIES measured, we used the near-bottom temperature, the resolution and accuracy of which are 0.01°C and 0.1°C, respectively. We also used temperature, velocity, and sea surface height data from the Hybrid Coordinate Ocean Model (HYCOM). We collected outputs from the HYCOM + NCODA Global 1/12° GOFS 3.1 41-layer analysis (GLBy0.08 Experiment ...